2018
DOI: 10.1080/13561820.2018.1498466
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of pharmacy students in Qatar toward interprofessional education and collaborative practice: a mixed methods study

Abstract: In an IPE environment, students are expected to have better understanding of the roles, responsibilities, and contribution of other health care professions to enhance interprofessional working and collaboration with an end result of improving patient-centred and team-based care. Although many studies have investigated students' attitudes, very few employ a mixed methods design and hardly are from Middle Eastern countries. A two-staged sequential explanatory mixed method design was used to comprehensively captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
2
20
0
Order By: Relevance
“…One of the key challenges highlighted in this study is the lack of collaborative practice in Qatar and the existence of a hierarchical system. This is similar to findings from others studies which focussed on pharmacy students and practising pharmacist perspectives toward IPE and collaborative practice in Qatar [45, 46]. Although IPE was perceived as an important component in overcoming this, it was also felt that these hierarchal differences could impede any initiatives, including IPE because of the more traditional attitudes and culture.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…One of the key challenges highlighted in this study is the lack of collaborative practice in Qatar and the existence of a hierarchical system. This is similar to findings from others studies which focussed on pharmacy students and practising pharmacist perspectives toward IPE and collaborative practice in Qatar [45, 46]. Although IPE was perceived as an important component in overcoming this, it was also felt that these hierarchal differences could impede any initiatives, including IPE because of the more traditional attitudes and culture.…”
Section: Discussionsupporting
confidence: 86%
“…An interesting finding in this study relates to the discussion around mixed gender education in IPE activities. Gender segregation in higher education is the norm in most public universities in the Gulf region [45, 52]. At Qatar University, undergraduate education is gender segregated except for the College of Medicine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it has been suggested that adopting a clearly defined scope of practice and recognizing the boundaries and limitations of the pharmacy profession could avert the issue of overlapping duties with physicians and other HCPs [17]. Another study that explored the perspectives of pharmacy students in Qatar on interprofessional education and collaborative practice, reported that pharmacy students were least confident about their professional identity [73]. This was attributed to lack of role models, existence of power and hierarchy between healthcare team members, and resistance to the evolving role of the pharmacists, especially by physicians [73].…”
Section: Discussionmentioning
confidence: 99%
“…Another study that explored the perspectives of pharmacy students in Qatar on interprofessional education and collaborative practice, reported that pharmacy students were least confident about their professional identity [73]. This was attributed to lack of role models, existence of power and hierarchy between healthcare team members, and resistance to the evolving role of the pharmacists, especially by physicians [73].…”
Section: Discussionmentioning
confidence: 99%